Optometric Care of the Patient with Diabetes - Hudson, Chris; Leong, Dianna; Loewen, Erin; MacDonald, Derek; Machmer, Angie; Mandadakis, Ken; Smit, Henry; Teliani, Nohad; Tousignant, Benoit (Canadian Journal of Optometry, 2017)
The Canadian Association of Optometrists (CAO) is the national voice of optometry and is dedicated to collaboratively advancing the highest standard of primary eye care through the promotion of optimal vision and eye health, in partnership with all Canadians. Optometrists are the front line of eye health and vision care. They are experts in primary eye care and are well-positioned to help combat the vision related complications of diabetes. CAO assembled the Diabetes Guidelines Working Group to create national guidelines on the clinical management of diabetes mellitus in an effort to further educate Canadian optometrists and assist them in the management of this chronic disease. The Working Group consists of optometrists from private practice, research and academia, chosen on the basis of their expertise, experience and representation from across Canada.